Analisis implementasi kebijakan sistem electronic customs declaration pada kantor pelayanan utama bea dan cukai tipe c soekarno hatta tahun 2022 sampai dengan 2024 - Citra Novlyani; Dwikora Harjo (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2025)
(Analysis of the Implementation of the Electronic Customs Declaration System Policy at the Soekarno Hatta Type C Main Customs and Excise Service Office from 2022 to 2024) This research analyzes the implementation of the Electronic Customs Declaration (e-CD) system at the Soekarno-Hatta Customs and Excise Main Service Office in 2022-2024. Soekarno-Hatta in 2022-2024. This research uses a qualitative qualitative method with a descriptive approach. Data was obtained through interviews with Customs officers, service users, and academics, as well as analyzing related documents. related documents. The results showed that implementation of e-CD has increased efficiency and transparency in the process of goods declaration. process of goods declaration. However, there are obstacles in its implementation, such as the low level of passenger awareness of declaration obligations, limited socialization, and technical challenges in the e-CD system. In addition, constraints also arise from the aspect of human resources, such as the number of officers who are still limited, especially during peak hours, as well as the need to increase the number of officers. limited number of officers, especially during peak hours, as well as the need to increase technical competence in managing the system. in managing the system. To overcome these obstacles, Soekarno-Hatta Customs has made various efforts, including increasing socialization through digital media and cooperation with airlines, optimizing the system with improvements to the airlines, optimizing the system by improving features and infrastructure, as well as strengthening training for officers. infrastructure, and strengthening training for officers. This research recommends a more massive socialization strategy and optimization of the verification system to increase service user compliance with regulations. verification system to improve service user compliance with customs regulations. Abstrak Penelitian ini menganalisis implementasi sistem Electronic Customs Declaration (e-CD) di Kantor Pelayanan Utama Bea dan Cukai Soekarno- Hatta pada tahun 2022–2024. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Data diperoleh melalui wawancara dengan petugas Bea Cukai, pengguna jasa, dan akademisi, serta analisis dokumen terkait. Hasil penelitian menunjukkan bahwa implementasi e-CD telah meningkatkan efisiensi dan transparansi dalam proses deklarasi barang. Namun, terdapat kendala dalam penerapannya, seperti rendahnya tingkat kesadaran penumpang terhadap kewajiban deklarasi, keterbatasan sosialisasi, serta tantangan teknis dalam sistem e- CD. Selain itu, kendala juga muncul dari aspek sumber daya manusia, seperti jumlah petugas yang masih terbatas terutama saat jam sibuk, serta perlunya peningkatan kompetensi teknis dalam mengelola sistem. Untuk mengatasi kendala tersebut, Bea Cukai Soekarno-Hatta telah melakukan berbagai upaya, antara lain peningkatan sosialisasi melalui media digital dan kerja sama dengan maskapai penerbangan, optimalisasi sistem dengan perbaikan fitur dan infrastruktur, serta penguatan pelatihan bagi petugas. Penelitian ini merekomendasikan strategi sosialisasi yang lebih masif dan optimalisasi sistem verifikasi guna meningkatkan kepatuhan pengguna jasa terhadap regulasi kepabeanan.